Assessment of pleiotropic effects of nebivolol: influence on microcirculation parameters and bone tissue in postmenopausal women with mild arterial hypertension - I. L. Tepojan; D. V. Nebieridze; I. A. Skripnikova; A. S. Safarjan; V. E. Novikov; L. M. Murashko; V. A. Vygodin (Кардиоваскулярная терапия и профилактика)
Aim. To assess influence of nebivolol on microcirculation (MC) and mineral density of bones (MDB) in postmenopausal women with mild arterial hypertension (AH) and osteopenia.Material and methods. To randomized controlled study were included 56 women of postmenopausal period at the age 50-65 y.o. with osteopenia and mild AH. During 12 months the main group (n=28) were taking nebivolol 2,5-5 mg, and controls (n=28) — atenolol 25-50 mg. At baseline and in 12 months clinical investigation was done, with anthropometry, blood pressure measurement, electrocardiogram registration, and qualitative MDB assessment via double energetic x-ray absorptiometry and assessment of MC with the application of computerized monochannel laser analyzer of capillary flow. In addition, we measured the levels of ionized calcium (Ca2+), total alkaline phosphatase (TAP), C-telopeptide of collagen I type (CTP).Results. At the background of mild AH therapy with nebivolol during 12 months there was increase of MDB in the spine by T-criterium from -1,7±0,4SD to -1,4±0,53 (р<0,001), in femoral cervix (FC) from -1,4±0,44SD to -1,27±0,5SD (р=0,015), in proximal part of femur (PPF) from -0,58±0,4SD to -0,49±0,4SD (р=0,003), however in control group on atenolol there was decrease of MDB of the spine by T-criteria from -1,5±0,7SD to -1,6±0,64SD (p<0,001), in FC from -1,3±0,64SD to -1,5±0,65 (р=0,0005), MDB of PPF was stable (р=0,3). In the main group there was difference of MC value by 107,4±11,2% (р<0,001) and MC effectiveness index by 318±53% (р<0,001), in control group MC value decreased by 15,7±8,5% (р=0,07), decrease of MC effectiveness index was not significant. During therapy, there was decrease of CTP in serum by 17,7±2,6% (р<0,001), though in control group this parameter increased by 44,7±11,2% (р<0,001). Dynamics of MDB in all studied regions, of MC parameters, of CTP level on therapy during 12 months significantly differed between main and control groups.Conclusion. In the study, we showed positive effect of nebivolol on MDB and MC.